Food trade openness and enhancement of food security: Partial equilibrium model simulations for selected countries - Fathelrahman, Eihab; Davies, Stephen; Muhammad, Safdar (MDPI, 2021)
This research measured the welfare impacts of food trade liberalization in India, Egypt, Pakistan, Saudi Arabia, and the United Arab Emirates (UAE) using the partial equilibrium model—World Integrated Trade Solution (WITS). Macroeconomic settings, domestic objectives, and food security indicator data are used to assess the implications of the simulations on food availability and stability. Simulation results for India, Egypt, and Pakistan indicate annual welfare gains (consumer surplus) of 2571, 340, and 25 million USD, respectively, while Saudi Arabia and the UAE have gains of 14 and 17 million USD. Results show that tariff elimination would have wide-ranging welfare impacts across food commodities within these countries. Moreover, reductions for specific commodities directly relevant to food energy and protein availability would have a greater direct impact on the poor. Lowering the highest tariffs on those commodities might raise the real incomes of more than 350 million persons by 7.5% or more and could create shifts in consumption towards more diversified and nutritionally sound diets.